FINANCIAL DISTRESS DAN KONEKSI POLITIK MEMODERASI PENGARUH AGRESIVITAS PAJAK DAN EKSPOSUR MEDIA TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - M. Wildan Rizkiawal, (2023)
This research is a quantitative study that aims to determine and test empirically the role of financial distress and political connections in moderating the effect of tax aggressiveness and media exposure on CSR disclosure. This study uses secondary data with a population of mining sector companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2021 period. The observational data of this study amounted to 140 data from 35 sample companies selected using the purposive sampling method and predetermined criteria. The research hypothesis was tested by multiple linear regression analysis using STATA version 14 with a significance level of 1%, 5% and 10%. The results of testing the hypothesis show that (1) tax aggressiveness has no effect on CSR disclosure, (2) media exposure has no effect on CSR disclosure, (3) financial distress does not moderate the effect of tax aggressiveness on CSR disclosure, but moderates the positive effect of media exposure on CSR disclosure, and (4) political connections are unable to moderate the effect of tax aggressiveness and media exposure on CSR disclosure.